2020
DOI: 10.1002/aorn.13281
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Team Familiarity: An Integrative Review

Abstract: The dynamic nature of perioperative care often brings unfamiliar clinicians together yet requires them to collectively provide complex health care in a challenging environment. In this review, we comprehensively evaluated evidence regarding surgical team familiarity and its relationship to surgical team performance. Using a comprehensive and iterative search strategy, we searched PubMed, Web of Science, PsycInfo, and EMBASE for surgical team familiarity manuscripts. We identified 598 manuscripts, 16 of which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Portanto, estudo mostra que o uso rotineiro dos checklists colabora para a familiarização da equipe cirúrgica na execução das etapas, otimizando a assistência cirúrgica e reduzindo o tempo operatório e de hospitalização 24 . Nesta pesquisa, a média do tempo de cirurgia passou de 138 minutos para 108 minutos; porém, ainda superior à análise de 165.474 artroplastias de quadril ou joelho, e cujos resultados mostraram Rev Col Bras Cir 50:e20233425 Batista Impacto de checklists cirúrgicos no tempo dos processos operatórios: um estudo transversal tempo operatório de aproximadamente 92 minutos 25 .…”
Section: Discussionunclassified
“…Portanto, estudo mostra que o uso rotineiro dos checklists colabora para a familiarização da equipe cirúrgica na execução das etapas, otimizando a assistência cirúrgica e reduzindo o tempo operatório e de hospitalização 24 . Nesta pesquisa, a média do tempo de cirurgia passou de 138 minutos para 108 minutos; porém, ainda superior à análise de 165.474 artroplastias de quadril ou joelho, e cujos resultados mostraram Rev Col Bras Cir 50:e20233425 Batista Impacto de checklists cirúrgicos no tempo dos processos operatórios: um estudo transversal tempo operatório de aproximadamente 92 minutos 25 .…”
Section: Discussionunclassified
“…We did not find any studies that had defined an adequate number of staff members needed on a surgical team or their composition per specific surgery. However, some studies did find that adequate surgical team size had a positive effect on teamwork, possibly because there are more people available to help complete tasks and share the total cognitive load (34,35). Adequate staffing can compensate for unexpected emergencies or prolonged surgical cases (36).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical teams are often constructed on an ad hoc basis and thus fluctuate, which can lead to a lack of familiarity (13). Familiarity enables a shared definition of teamwork and professional roles that can increase positive surgeon-anesthesiologist relationships (14,34). Doll et al (41) found that a managerial decision to assign a particular anesthetist to a surgeon and to use a predefined surgical list resulted in decreased operative times.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to improve intraoperative communication and efficiency have been proposed, such as implementing a structured plan for each procedure 9 . Across several disciplines, having a consistent team in the operating room (OR) has been shown to improve task‐specific communication, decrease procedure duration and disruptions, and improve postoperative outcomes 10,11 . However, the utility of team consistency has not been outlined in the head and neck literature.…”
Section: Introductionmentioning
confidence: 99%